The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/732644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intersecting vulnerabilities: Climatic and demographic contributions to future population exposure to Aedes-borne viruses in the United States

Abstract: Understanding how climate change and demographic factors may shape future population exposure to viruses such as Zika, dengue, or chikungunya, transmitted by Aedes mosquitoes is essential to improving public health preparedness. In this study, we combine projections of cumulative monthly Aedes-borne virus transmission risk with spatially explicit population projections for vulnerable demographic groups (age and economic factors) to explore future county-level population exposure across the conterminous United … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition to climate factors, human population contributions to the expansion of Aedes aegypti and future population exposure to Aedes-borne virus might also be of large importance (Rohat et al, 2020). Our model revealed that a future human population change significantly influences the climate-based predictions (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In addition to climate factors, human population contributions to the expansion of Aedes aegypti and future population exposure to Aedes-borne virus might also be of large importance (Rohat et al, 2020). Our model revealed that a future human population change significantly influences the climate-based predictions (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Our model is an extension of a previous model (Liu-Helmerssne et al, 2019a) by incorporating predicted population patterns into the mosquito's life history traits. This incorporation makes our model advantageous over previous models where predicted population patterns were merely used to estimate future population vulnerability and nearly independent of the mosquito's life history (Monaghan et al, 2018;Kraemer et al, 2019;Messina et al, 2019;Rohat et al, 2020), in terms of minimizing skewed estimates of climatic impacts across different SSPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the field of climate-sensitive vector borne diseases studies, the overwhelming majority of risk assessments are still superimposing RCPs-based climate projections on the current state of the society (e.g. Ryan et al, 2019)although a few recent exceptions must be pointed out (Monaghan et al, 2018;Messina et al, 2019;Rohat et al, 2019d). This is particularly problematic because socioeconomic development -and in particular migration, urbanization, economic development, and population growth -are thought to be key drivers of the spread of vector-borne diseases.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%